2011
DOI: 10.4236/ajps.2011.24062
|View full text |Cite
|
Sign up to set email alerts
|

DNA Finger Printing of <i>Prosopis cineraria</i> and <i>Prosopis juliflora</i> Using ISSR and RAPD Techniques

Abstract: Diversity within and among the populations of Prosopis cineraria and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…ISSR-polymerase chain reaction (PCR) is a technique that involves the use of microsatellite sequences as primers in PCR to generate multi-locus markers. ISSR markers are highly polymorphic and are useful in studies of genetic diversity, phylogeny, genetic marking, genome mapping, and evolutionary biology (Elmeer and Almalki, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…ISSR-polymerase chain reaction (PCR) is a technique that involves the use of microsatellite sequences as primers in PCR to generate multi-locus markers. ISSR markers are highly polymorphic and are useful in studies of genetic diversity, phylogeny, genetic marking, genome mapping, and evolutionary biology (Elmeer and Almalki, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In later years, PAST has grown into a comprehensive statistics package that is used not only by paleontologists, but also in many fields of life science, earth science, and even engineering and economics (Hammer et al, 2001). PAST program was used in DNA fingerprinting (ISSR and RAPD) of Prosopis cineraria and P.juliflora (Elmeer and Almalki, 2011), molecular (SSR) analysis of old apple cultivars (Király et al, 2012), genetic analysis (RAPD) of Hibiscus species (Kadve et al, 2012), molecular (SSR) determination of genetic structure of Brazilian soybean cultivars (Piriolli et al, 2013), SSR-based genetic diversity assessment in tetraploid and hexaploid wheat populations (Abouzied et al, 2013), molecular diversity (SSR) in cultivated groundnut (Goswami et al, 2013). …”
Section: Resultsmentioning
confidence: 99%
“…Several authors have reported the efficiency of using both types of markers (Ranade et al, 2009;Elmeer and Almalki, 2011;Mani et al, 2011;Sharma et al, 2010Sharma et al, , 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmawati et al (2004) evaluated the diversity among 16 genotypes of Grevillea using RAPD markers and found an average of 17.34 polymorphic bands per primer. Elmeer and Almalki (2011) assessed the genetic diversity of Prosopis cineraria and P. juliflora using RAPD markers and found 100% polymorphism. In this study, the PIC of the RAPD primers varied from 0.257 to 0.490, with an average of 0.364.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation